Microfluidic Nanoparticles for Drug Delivery. Issue 36 (9th April 2022) - Liu, Yun; Yang, Guangze; Hui, Yue; Ranaweera, Supun; Zhao, Chun‐Xia
Abstract: Nanoparticles (NPs) have attracted tremendous interest in drug delivery in the past decades. Microfluidics offers a promising strategy for making NPs for drug delivery due to its capability in precisely controlling NP properties. The recent success of mRNA vaccines using microfluidics represents a big milestone for microfluidic NPs for pharmaceutical applications, and its rapid scaling up demonstrates the feasibility of using microfluidics for industrial‐scale manufacturing. This article provides a critical review of recent progress in microfluidic NPs for drug delivery. First, the synthesis of organic NPs using microfluidics focusing on typical microfluidic methods and their applications in making popular and clinically relevant NPs, such as liposomes, lipid NPs, and polymer NPs, as well as their synthesis mechanisms are summarized. Then, the microfluidic synthesis of several representative inorganic NPs (e.g., silica, metal, metal oxide, and quantum dots), and hybrid NPs is discussed. Lastly, the applications of microfluidic NPs for various drug delivery applications are presented. Abstract : Microfluidics offers a promising strategy for making nanoparticles for drug delivery due to its capability in precisely controlling nanoparticle properties. This article provides a critical review of recent progress in microfluidic nanoparticles for drug delivery. Different microfluidic synthesis technologies and mechanisms of organic, inorganic, and hybrid nanoparticles, as well as their various drug delivery applications are summarized.